Diet of the white-dotted skate, Bathyraja albomaculata, in waters of Argentina - Ruocco, Natalia Lorena (2009)
The present paper analyzes the diet, feeding strategy and niche width of Bathyraja albomaculata over the Patagonian continental shelf and upper slope. The diet comprised a variety of 14 small invertebrates, although the most important prey were polychaete worms. The opheliid polychaete Travisia sp. and the gammarid amphipod Cirolana sp. were the main prey present in stomach contents of B. albomaculata. No differences were found between the diets of males and females, however ontogenetic changes were detected. Skates <40 cm of disk width (DW) preyed on amphipods, and sizes >40 cm DW largely consumed polychaetes. As size increased, polychaetes became more important and the importance of amphipods decreased. B. albomaculata showed a narrow food niche and a marked specialization towards polychaetes.